A Meta-Analysis of Studies on Museum Trips in Education - Kan, Çiğdem (İstanbul Medeniyet Üniversitesi, 2022)
The present study was conducted to review the contribution of museum trips to learning and teaching, the problems experienced in museum trips, and possible solutions to these problems. The papers listed on Google academic search engine, EBSCOhost and Dergipark databases were reviewed. The study sample included 12 papers selected based on the aim of the study from 65 articles on museums published between 2012 and 2021, and meta-synthesis (thematic content analysis) was conducted on these papers. The analysis was based on the contribution of museum visits to the learning and teaching, associated problems, and the solution recommendations. Thus, the participant views and suggestions were listed. The most common view on the contribution of museum visits to the learning and teaching was that the educational museum visits increased the interest of the students in the course and ensures permanence. The most common statement on the problems experienced in museum visits was that the limited knowledge of the teachers about the concept of museum education, and unawareness about the related applications, and the unplanned character of the museum visits. The most common recommendations of the authors included in-service training for the teachers and other stakeholders about the museums.

Bu araştırma, müze gezilerinin öğrenme-öğretme sürecine katkıları, müze gezileri konusunda yaşanan sorunlar ve çözüm önerilerini derlemek amacıyla yapılmıştır. Meta-sentez (tematik içerik analizi) yönteminin kullanıldığı araştırmanın örneklemini, nitel araştırma yöntemleriyle çalışılmış ve müze gezileri konusunda yaşanan sorunlar ve çözüm önerilerini içeren 2012-2021 yılları arasında yayınlanmış 12 makaleden oluşmaktadır. Çalışmada müze ziyaretlerinin öğrenme-öğretme sürecine katkıları, müze ziyaretlerinin yeterli düzeyde yapılmamasının nedenleri ve katılımcıların önerileri boyutlarına göre analiz edilmiştir. Bu amaçla görüş ve öneriler listelenmiştir. Müze gezilerinin öğrenme-öğretme sürecine katkıları konusunda en fazla belirtilen ifade; eğitsel müze gezilerinin öğrencilerin derse ilgisini arttırdığı ve kalıcılığı sağladığı; müze gezileri konusunda yaşanan sorunlar hakkında en fazla belirtilen ifade; Öğretmenlerin müze eğitimi kavramını yeterince bilmedikleri ve uygulamalardan haberdar olmadıkları, bilgi eksiklikleri ve müze gezilerinin plansız bir şekilde yapıldığı; Araştırmacıların, müzelerle ilgili önerileri konusundaki en fazla belirtilen ifadeler; müzeler konusunda öğretmenlere hizmetiçi eğitim ve bütün paydaşlara yönelik eğitim verilmesi şeklinde belirtilmiştir.
Eğitimde Müze Gezilerini Konu Edinen Çalışmaların Meta Sentez Yöntemiyle İncelenmesi
Keywords: Library and Information Studies; Kütüphane ve Bilgi Çalışmaları